2019
DOI: 10.3390/ijms20051169
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Menadione on Helicobacter pylori Growth and Helicobacter pylori-Induced Inflammation via NF-κB Inhibition

Abstract: H. pylori is classified as a group I carcinogen by WHO because of its involvement in gastric cancer development. Several reports have suggested anti-bacterial effects of menadione, although the effect of menadione on major virulence factors of H. pylori and H. pylori-induced inflammation is yet to be elucidated. In this study, therefore, we demonstrated that menadione has anti-H. pylori and anti-inflammatory effects. Menadione inhibited growth of H. pylori reference strains and clinical isolates. Menadione red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…However, TLR2 (but not TLR4) has been reported as essential for H. pylori ‐induced NF‐κB activation and chemokine expression by epithelial cells 37 . Chronic gastritis is induced by H. pylori infection through virulence factors, such as CagA and VacA, which induce the NF‐κB signaling pathway by activating inflammatory factors, including IL‐8 and TNF‐α 5,38 . Our results revealed that H. pylori significantly increased the phosphorylation of the NF‐κB p65 subunit as well as the degradation and phosphorylation of IκBα, which was similar to previous reports 39 .…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, TLR2 (but not TLR4) has been reported as essential for H. pylori ‐induced NF‐κB activation and chemokine expression by epithelial cells 37 . Chronic gastritis is induced by H. pylori infection through virulence factors, such as CagA and VacA, which induce the NF‐κB signaling pathway by activating inflammatory factors, including IL‐8 and TNF‐α 5,38 . Our results revealed that H. pylori significantly increased the phosphorylation of the NF‐κB p65 subunit as well as the degradation and phosphorylation of IκBα, which was similar to previous reports 39 .…”
Section: Discussionmentioning
confidence: 70%
“…Chronic inflammation is considered an important inducer of tumor development. H. pylori induces gastric epithelial inflammation through different virulence factors, such as cytotoxin‐associated protein A (CagA), vacuolating cytotoxin A (VacA) and lipopolysaccharide (LPS), and induces NF‐κB nuclear translocation and IL‐8 production 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…Pro-inflammatory cytokine production occurs during H. pylori infection, with the inflammatory reactions potentially leading to chronic inflammation rather than eliminating H. pylori (38,39). The transcription factor NF-κB can be activated by IL-1β, LPS, peptidoglycan and tumor necrosis factor-α during H. pylori infection (40). NF-κB is critical modulator of cytokine expression (41).…”
Section: Discussionmentioning
confidence: 99%
“…Upon activation of NF-κB, the transcription of a number of inflammatory genes can be activated, e.g., tumor necrotic factor alpha (TNF-α), interleukin-1β (IL-1β), interleukin-6 (IL-6), inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), monocyte chemoattractant protein-1 (MCP-1), etc. [1,[16][17][18][19]. This is the basic functional mechanism through which the NF-κB transcription factor induces an inflammatory response.…”
Section: Introductionmentioning
confidence: 99%